2007
DOI: 10.1200/jco.2007.25.18_suppl.8051
|View full text |Cite
|
Sign up to set email alerts
|

Schedule of bortezomib administration may be an important determinant of single-agent activity in patients with relapsed or refractory follicular (FL) lymphoma and mantle cell lymphoma (MCL)

Abstract: 8051 Background: We previously demonstrated the significant activity of bortezomib for the treatment of FL and MCL. The activity in MCL has been confirmed in a multi-center study leading to the recent approval by the FDA. The demonstrated activity was observed on the twice weekly schedule. Recent data using bortezomib in combination with rituximab suggested that weekly bortezomib was less toxic and possibly equally as efficacious as twice weekly bortezomib. This study does not allow a determination of weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…The incidence and severity of neuropathy were similar in the two groups of patients. Equivalent degrees of neurotoxicity have likewise been observed in other reports where bortezomib has been given once or twice weekly (Goy et al , 2005; O’Connor et al , 2005, 2007; Fisher et al , 2006; Strauss et al , 2006; Gerecitano et al , 2009; de Vos et al , 2009).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The incidence and severity of neuropathy were similar in the two groups of patients. Equivalent degrees of neurotoxicity have likewise been observed in other reports where bortezomib has been given once or twice weekly (Goy et al , 2005; O’Connor et al , 2005, 2007; Fisher et al , 2006; Strauss et al , 2006; Gerecitano et al , 2009; de Vos et al , 2009).…”
Section: Discussionsupporting
confidence: 61%
“…However, a subsequent multi‐centre trial (in MCL) suggested a rather lower response rate (31%), with a median duration of response of 9 months in a heavily pre‐treated population (Fisher et al , 2006). Again, the principal toxicities were gastro‐intestinal (GI) tract symptoms, peripheral neuropathy and thrombocytopenia (Goy et al , 2005; O’Connor et al , 2005, 2007; Fisher et al , 2006; Strauss et al , 2006; Gerecitano et al , 2009; de Vos et al , 2009).…”
mentioning
confidence: 99%
“…Despite this, only 4 patients had a dose change in either bortezomib or vincristine solely due to neuropathy. The incidence of neuropathy (all grades and ≥grade3) reported in this trial is broadly similar to that reported in other trials of weekly bortezomib administration in MCL patients (De Vos et al , ), and is lower than that reported in some trials of biweekly bortezomib (Goy et al , ; O'Connor et al , , ; Fisher et al , ; Strauss et al , ; De Vos et al , ; Gerecitano et al , ). This conflicts with the results from a randomized phase II trial of bortezomib + RCHOP (Ribrag et al , ), which reported increased peripheral neuropathy when higher dose bortezomib (weekly dose 1·6 mg/m 2 ) was used, but acceptable toxicity with lower dose bortezomib (1·3 mg/m 2 bi weekly).…”
Section: Discussionsupporting
confidence: 87%
“…Recent data shows an improvement in survival of MCL patients when rituximab is added to fludarabine‐cyclophosphamide chemotherapy. (Rule et al , ) Given that bortezomib appears to have significant single agent activity in MCL (O'Connor et al , ; Goy et al , ) and has an acceptable toxicity profile when combined with CHOP chemotherapy, it is now being combined with RCHOP immunochemotherapy in trials. The PFS of CHOP‐bortezomib in a relapse setting is virtually identical to that of RCHOP given in a first line setting (Howard et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…46%). Our experience with bortezomib in patients with follicular lymphoma clearly demonstrated that patients with refractory disease exhibited a much shorter PFS compared with patients with relapsed disease (7·5 months vs. 1·8 months) (O’Connor et al , 2007). Interestingly, in MCL it appears that bortezomib may be capable of overcoming both the intrinsic and acquired mechanisms of drug resistance in some relatively consistent fraction of patients.…”
Section: Discussionmentioning
confidence: 99%